Chinese classics Zhao the orphan - Ji Junxiang (Chinese classics stories, 2017)
Zhao the Orphan is a Chinese play of the Yuan Dynasty, attributed to Ji Junxiang, written in the second half of the 13th century. In it the hero sacrifices his son to save the life of young Zhao so that Zhao can later avenge the death of his family. It is the first Chinese play known in Europe. This book is edited and translated by the famous translator Wang Guozhen, to introduce Zhao the Orphan to the foreign readers.